The role of import substitution innovation centers in strengthening technological independence and stimulating innovation in automotive components production - Lyachenkov, M. I. (Вестник университета, 2025)
Modern conditions affecting regional social and economic systems development have been studied, which acquire a special significance and role for import substitution innovation centers creation. These centers will strengthen technological independence and stimulate innovation in automotive components production, which will contribute to a more successful regional economic systems development. The relevance of the topic and the purpose of the study is to assess the role of import substitution innovation centers in strengthening technological independence and stimulating innovation in automotive components production. The subject of the study is organizational and economic relations arising in implementation of import substitution innovation centers in strengthening technological independence and stimulating innovation in automotive components production. Common scientific methods were used, including comparative analysis and interdependencies identification. The leading approach to the study is the theoretical approaches assessment that promote practical implementation of import substitution in automotive components production through innovation centers in Russian regional systems. Based on the scientists’ works it has been concluded that the process of creating innovation centers for import substitution helps to solve one of the key tasks facing the state, in particular, providing the market with domestic goods that replace import.